GAD-7 and PHQ-9 measurement of perinatal anxiety and depression in women with hypertensive disorders of pregnancy in Yaounde, Cameroon - Essiben, Felix; Um, Esther Meka Ngo; Ojong, Samuel; Gimnwi, Felix; Olen, Kamga; Nana, Philip Njotang (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The aim of the study was to determine the prevalence of perinatal anxiety and depression in women with hypertensive diseases during pregnancy in Yaounde. Methods: Authors carried out a cross-sectional descriptive study over nine months from October 2015 to May 2016, amongst pregnant women with hypertensive pregnancy disorders followed up in three tertiary care centers in Yaounde. Authors collected information from the medical files of selected patients by using a pre-tested and validated questionnaire in the perinatal period. We classified blood pressure values as per the JNC 7 recommendations. Anxiety and mental depression were evaluated for using the Generalized Anxiety Disorder 7-item and the Patient Health Questionnaires-9 respectively. Data analysis was done using CSPro version 6.2 and SPSS version 20.0 software. Results: Authors included 202 patients during the study period. The mean age stood at 25.9± 6.4years (extremes 13-43years). Amongst these, 47.5% were single while 97.5% (197/202) had received at least primary education. Students represented 45.5% (92/202) of women while 102 (50.5%) of them had some form of employment in the public, private or informal sectors. Severe preeclampsia was the most prevalent hypertensive disorder in these women, with 69 (34.2%) developing eclampsia. We found that 79% (161/202) of these patients suffered from anxiety, 67.3% (136/202) were depressive while 61.3% (124/202) had both anxiety and depression. Conclusions: The prevalence of perinatal anxiety and depression in women with hypertensive pregnancy disorders is high. Associated factors must be looked out in order to prevent these situations.